2013
DOI: 10.1017/s1368980013001705
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of household food insecurity of First Nations people living in an on-reserve, sub-Arctic community within the Mushkegowuk Territory

Abstract: Objective: To measure and describe the prevalence and severity of household food insecurity in a remote on-reserve First Nations community using the Household Food Security Survey Module (HFSSM) and to evaluate the perceived relevance of the HFSSM for this population. Design: Household food security status was determined from the eighteen-item HFSSM following the classifications developed by Health Canada for the Canadian Community Health Survey, Cycle 2?2 Nutrition. One adult from each household in the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 28 publications
2
56
0
1
Order By: Relevance
“…Critics noted that this program was tailored to what is considered a healthy lifestyle by "outsiders" and there is little control over produce quality [10,17]. Despite attempts from the Canadian Government to improve food security in northern communities, recent research in one remote First Nation community revealed that most respondents interviewed worried about having enough food and if they could afford to eat balanced meals [18].…”
Section: Current Food Systems In Northern Canadian Aboriginal Communimentioning
confidence: 99%
“…Critics noted that this program was tailored to what is considered a healthy lifestyle by "outsiders" and there is little control over produce quality [10,17]. Despite attempts from the Canadian Government to improve food security in northern communities, recent research in one remote First Nation community revealed that most respondents interviewed worried about having enough food and if they could afford to eat balanced meals [18].…”
Section: Current Food Systems In Northern Canadian Aboriginal Communimentioning
confidence: 99%
“…At the sub-national level, food insecurity is disproportionately experienced by certain groups, particularly Indigenous Peoples (Egeland, Johnson-Down, Cao, Sheikh, & Weiler, 2011;Skinner, Hanning, & Tsuji, 2014;Rosol et al, 2011;Willows et al, Kuhle, 2011). For Inuit, adverse health effects include (but are not limited to) disrupted eating patterns, reduced diet quality and increased susceptibility to chronic and infectious disease (Egeland et al, 2011;Huet, Rosol, & Egeland, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…L'incidence et la gravité de l'insécurité alimentaire étaient variables, avec des taux généralement plus élevés dans les collectivités accessibles unique ment par avion que dans celles accessibles par la route ou par chemin de fer 12 . De même, d'après une étude menée en 2013 sur la Première nation de Fort Albany, établie le long de la côte de la baie James dans ce qui constitue aujourd'hui le nord de l'Ontario, 70 % des ménages vivaient dans l'insécurité alimentaire 13 . 14,15 .…”
Section: Contexteunclassified